Analysis and optimization of selective laser sintering for thermoplastic polyurethane - Leong, Jieyong (2015)
Since the introduction of Additive Manufacturing (AM), many researches have been done over the decades on the technology and practicality of 3D-printing. Various materials with a wide range of properties have been developed for AM, but there are limited polymers available for selective laser sintering (SLS) for commercial purposes. Previous explorations of polymers show that most of the thermoplastics for SLS are stiff and rigid engineering polymers such as polyamide 12 and polystyrene. Recently, thermoplastic polyurethane (TPU) is introduced to the SLS system to bridge the gap of material properties, because TPU is a semi-crystalline elastomer material which has similar flexibility and toughness as in rubbers. In 2012, the Desmosint® X92 is a newly developed TPU powder for the SLS process by Bayer Material Science and Solid Composites GmbH. The purpose of this project is to test the effects of laser power, processing speed, hatching and sintering bed temperature on the material properties of Desmosint® X92 powder after the SLS process. The machine used to perform the 3D-printing for this experiment is the EOSINT P 395. Two settings will be assigned to each testing parameters and a Design of Experiment (DOE), specifically the Analysis of Variance (ANOVA) method, is used to investigate the results after putting the samples through a tensile test. Load at break, tensile stress and strain at break, strength at break and Young’s modulus are the responses collected from the tensile testing of printed samples. From the results and discussion of the experiments, hatch spacing have had a significant impact on the structural integrity of the printed samples while laser power also played a major role on the improvement of mechanical properties of sintered specimens. The decrease in bed temperature saw a general decline in the all collected result parameters. This experiment has developed an optimised model for laser sintering the new TPU powder to ensure the highest performance of the material properties.